Computer-generated rough sex: An empirical study about the interest in human and artificial sexually explicit media displaying rough and gentle sexual behaviors - Jessica M. Szczuka; Natalia Szymczyk (Studies in Communication, Media)
Computer-generated sexually explicit media is on the rise. While previous studies suggest that human sexualized stimuli are preferred compared to artificial ones, these studies did not consider the depicted sexual behavior as an influential factor. This, however, could be crucial because when individuals consume rough sexualized behavior, some tend to detach the humanity of the performers anyhow, raising the question about the significance of humanity within such sexualized entertainment media. To determine whether the explicitly stated interest in artificial and human sexualized stimuli depends on the displayed sexual behavior, a within-subject online experiment was conducted in the summer of 2022 with 274 heterosexual participants (152 men, 122 women). Further analyses with N = 68 individuals identifying as homosexual (N = 39 male and N = 29 female) are included. A key finding from the research indicates that heterosexual individuals show a preference for computer-generated rough SEM compared to depictions involving humans. This study provides preliminary evidence suggesting that the portrayal of sexual behavior is pivotal in the acceptance of artificial sexual stimuli. It also delves into the potential of these materials as an extension for sexual satisfaction, yet it raises new questions that warrant further exploration.